Molecular basis for intestinal mucin recognition by galectin-3 and C-type lectins - Leclaire, Charlotte; Lecointe, Karine; Gunning, Patrick A; Tribolo, Sandra; Kavanaugh, Devon W; Wittmann, Alexandra; Latousakis, Dimitrios; MacKenzie, Donald A; Kawasaki, Norihito; Juge, Nathalie (The FASEB journal, 2018)
Intestinal mucins trigger immune responses upon recognition by dendritic cells via protein-carbohydrate interactions. We used a combination of structural, biochemical, biophysical, and cell-based approaches to decipher the specificity of the interaction between mucin glycans and mammalian lectins expressed in the gut, including galectin (Gal)-3 and C-type lectin receptors. Gal-3 differentially recognized intestinal mucins with different O-glycosylation profiles, as determined by mass spectrometry (MS). Modification of mucin glycosylation, via chemical treatment leading to a loss of terminal glycans, promoted the interaction of Gal-3 to poly- N-acetyllactosamine. Specific interactions were observed between mucins and mouse dendritic cell-associated lectin (mDectin)-2 or specific intercellular adhesion molecule-grabbing nonintegrin-related-1 (SIGN-R1), but not mDectin-1, using a cell-reporter assay, as also confirmed by atomic force spectroscopy. We characterized the N-glycosylation profile of mouse colonic mucin (Muc)-2 by MS and showed that the interaction with mDectin-2 was mediated by high-mannose N-glycans. Furthermore, we observed Gal-3 binding to the 3 C-type lectins by force spectroscopy. We showed that mDectin-1, mDectin-2, and SIGN-R1 are decorated by N-glycan structures that can be recognized by the carbohydrate recognition domain of Gal-3. These findings provide a structural basis for the role of mucins in mediating immune responses and new insights into the structure and function of major mammalian lectins.-Leclaire, C., Lecointe, K., Gunning, P. A., Tribolo, S., Kavanaugh, D. W., Wittmann, A., Latousakis, D., MacKenzie, D. A., Kawasaki, N., Juge, N. Molecular basis for intestinal mucin recognition by galectin-3 and C-type lectins.